Emphasizing grid feature as flood zonal identification to support flood relief mechanism - Ahmad, Zuhairi; Shammodin, Muhammad Shaheed; Singh, Ranjit (Universiti Teknologi Malaysia, 2017)
Annual flood outbreaks during Northeast monsoon season in the East Coast of Peninsular Malaysia are known to be a prevalent issue. More research and studies incorporating Geographic Information System (GIS) approach have been invested by the government to lessen Malaysia’s economic strain. This study will elaborate on how gridding feature is essential in flood mapping while focusing on Pekan sub district as the case study area. Methodology: The methodology consists of combining a generated 3-Dimensional map model with multiple blank layers acting as river water level. A simple survey procedure was conducted to convert MyGeiod mean sea level (MSL) to GPS ellipsoidal height (WGS84) by ratio calculation. River water levels are then to be offset by 1.0m each starting from 2.5 meter (danger level, Pekan station; ID 3434401) to 5.5 meter height. Grids were set at 250m x 250m squares focusing only within the study area boundaries and the inundated areas are populated and observed from the river water simulation. Findings: The 3-Dimensional map model of Pekan sub-district provides terrain information of the area while combining it with multiple layer offsets allow inundation to be simulated. Flood zones are identified and marked where results indicate significant flood effect at 3.5m (in which 3.66m is the danger level). While at 5.5m gauge reading, Pekan subdistrict is observed to be totally inaccessible from the three main routes (Pekan-Rompin, Pekan-Balik Batu, and Pekan-Kuantan). Contribution: The graphical output that are produced are then used to assess the rate of accessibility and affected infrastructures which have the potential to act as flood relief center. Integrating these information with disaster web information provider like ‘infobanjir’ (DID) and ‘disaster portal’ (NADMA) should be emphasized to ensure systematic flood management in the future.